2015
DOI: 10.1515/ijfe-2014-0264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooking Temperature on Mineral Content and Anti-nutritional Factors of Yam and Taro Grown in Southern Ethiopia

Abstract: This study aimed to determine the mineral composition and anti-nutritional factors, oxalate and phytate, of yam and taro grown in southern Ethiopia. In addition, the effect of cooking at different temperatures on the mineral compositions and anti-nutritional factors together with respective molar ratios Ca:oxalate, Zn:phytate, Ca:phytate and (Ca  phytate):Zn was determined. The mineral compositions were found to be: 21.8-15.7, 0.65-0.95, Co; and 0.18-0.68 Ni in mg/100 g of raw taro samples. Mineral content de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Plant-based diets are often associated with micronutrient deficits, exacerbated in part by poor micronutrient bioavailability. The diet-related factors have a greater influence on the bioavailability of the micronutrients Chemistry International 4(1) (2018) [15][16][17][18][19][20][21][22][23] Effect of cooking time on selected metals, oxalate and phytate contents of the raw and cooked lettuce from five farms in Ethiopia in plant foods, particularly Ca, Fe and Zn, than on the macronutrients (Mohite et al 2013;Ayele et al, 2015). Phytate has been recognized as an anti-nutrient due to its adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant-based diets are often associated with micronutrient deficits, exacerbated in part by poor micronutrient bioavailability. The diet-related factors have a greater influence on the bioavailability of the micronutrients Chemistry International 4(1) (2018) [15][16][17][18][19][20][21][22][23] Effect of cooking time on selected metals, oxalate and phytate contents of the raw and cooked lettuce from five farms in Ethiopia in plant foods, particularly Ca, Fe and Zn, than on the macronutrients (Mohite et al 2013;Ayele et al, 2015). Phytate has been recognized as an anti-nutrient due to its adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is desirable to establish optimum time and temperature to process food in order to derive maximum health benefits. Ayele et al (2015) have reported the effect of cooking temperature on mineral content and antinutritional factors of yam and taro grown in southern Ethiopia. The study showed significant decrease in the phytate and oxalate contents of yam and taro on cooking and increase in the bioavailability of minerals in the cooked samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of elements in plants, generally, depend on many factors; species, age, root distribution of the plant, physical and chemical nature of the soil, proportions and distributions of elements and the general climatic conditions [20][21][22][23][24]. Under most conditions, metallic elements that enter animals are those contained in plants eaten or used as a beverage either directly or indirectly [19,25,26]. Thus, the metal content of edible plants frequently controls the amount of these elements available in different animal bodies.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that almost all mineral element concentrations in peel were higher than those in tissue. A lot of investigations on elemental content of yam were carried out in Nigeria (Okwu and Ndu, 2006;Ayele, 2009;Ameh, 2007;Karim et al, 2013;Olajumoke et al, 2014). Other studies were conducted mainly in India (Shanthakumari et al, 2008), South Korea (Shin et al, 2012), Ghana (Dufie et al, 2013;Polycarp et al, 2012), Cote d'Ivoire (Kouadio et al, 2013), etc., where AAS and ICP-AES have been widely used to determine mineral elemental content.…”
Section: Introductionmentioning
confidence: 99%